Metal lithium negative electrode of composite polymer electrolyte protective layer and preparation method of metal lithium negative electrode

By forming a composite polymer electrolyte protective layer on the cellulose film of the metal lithium negative electrode, the problems of uniform deposition of lithium and interface stability are solved, and the cycle life and safety performance of the battery are significantly improved.

CN119786542AActive Publication Date: 2025-04-08CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411968849.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The prior art is difficult to solve the problems of uniform deposition and interface stability of metal lithium negative electrodes, resulting in reduced battery safety and shortened service life.

Method used

Using the preparation method of metal lithium negative electrode with a composite polymer electrolyte protective layer, a uniform protective layer is formed by spraying ZnO-graphene or ZnS-graphene nanocomposite aqueous solution on a cellulose film and spraying a liquid precursor thereon, and a uniform protective layer is formed by photoinduced polymerization.

Benefits of technology

Promote uniform deposition of lithium, enhance interface stability, improve battery cycle life and safety performance, simplify manufacturing processes, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786542A_ABST
    Figure CN119786542A_ABST
Patent Text Reader

Abstract

The invention discloses a metal lithium negative electrode of a composite polymer electrolyte protective layer and a preparation method of the metal lithium negative electrode, and relates to the technical field of lithium batteries. The method comprises the following steps: firstly, spraying graphene nano materials of nano ZnO and ZnS on the surface of a cellulose membrane in advance, spraying the materials on the cellulose membrane through an aqueous solution to ensure uniform distribution, then drying the treated cellulose membrane, pressing the cellulose membrane on the surface of a lithium foil (or a metal lithium alloy foil) negative electrode, and in the follow-up roll-to-roll walking process, carrying out roll-to-roll walking on the surface of the lithium foil (or the metal lithium alloy foil) negative electrode. A liquid precursor capable of being cured in situ is sprayed on the surface of metal lithium, and finally, a uniform polymer electrolyte protective layer is formed through photo-initiation polymerization. Due to the existence of the cellulose membrane, the liquid precursor can be quickly and uniformly dispersed, and sliding and local aggregation are avoided, so that a polymer electrolyte protection layer formed after photo-initiation polymerization is smooth and uniform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a metal lithium negative electrode with a composite polymer electrolyte protective layer and a preparation method thereof, aiming to significantly improve the interface cycle stability of the metal lithium negative electrode and the overall performance of the battery. Background Art

[0002] Metallic lithium has attracted much attention as a negative electrode material due to its high theoretical specific capacity and low potential, but it faces many challenges in practical applications, such as lithium dendrite formation and interface instability, which lead to reduced battery safety and shortened battery life.

[0003] CN202211432565.8 A double-layer protective layer of metallic lithium and a method for modifying the interface of a metallic lithium negative electrode, by simply immersing lithium foil in a solution of a fluorine-containing metal salt, and after drying, spontaneously forming in situ as a negative electrode through a charge / discharge process, and the preparation method is simple. A double-layer interface containing lithium fluoride and a lithium-containing alloy is formed on the surface of metallic lithium. This double-layer interface can provide uniformly distributed lithium-philic sites, promote uniform nucleation and deposition of lithium, improve the stability of metallic lithium negative electrodes, promote rapid diffusion of lithium ions, effectively inhibit the growth of lithium dendrites, and improve the safety performance and cycle stability of metallic lithium batteries.

[0004] However, it is difficult to evenly distribute the fluorine-containing metal salt on the surface of lithium foil by simply immersing it in the above method, and it is difficult for traditional protection methods to simultaneously solve the problems of uniform lithium deposition and interface stability. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a metal lithium negative electrode with a composite polymer electrolyte protective layer and a preparation method thereof, which stabilizes the interface of the metal lithium negative electrode and provides a new idea for improving the performance of the metal lithium negative electrode.

[0006] The present invention is achieved by a method for preparing a metal lithium negative electrode with a composite polymer electrolyte protective layer, which comprises the following steps in sequence:

[0007] (1) spraying a layer of ZnO-graphene nanocomposite aqueous solution or ZnS-graphene nanocomposite aqueous solution on the surface of the cellulose film;

[0008] (2) laminating a layer of the cellulose film prepared in step (1) on the surface of the negative electrode of lithium foil or metal lithium alloy foil;

[0009] (3) spraying a liquid precursor that can be cured in situ on the cellulose film, and forming a metal lithium negative electrode with a uniform composite polymer electrolyte protective layer through photoinitiated polymerization.

[0010] The thickness of the lithium foil or metal lithium alloy foil is in the range of 10-80 microns.

[0011] The thickness of the cellulose film is in the range of 0.5-5 microns.

[0012] The concentration of the ZnO-graphene nanocomposite aqueous solution or the ZnS-graphene nanocomposite aqueous solution is 0.1 mg / ml-1 mg / ml, and the spraying amount is controlled at 0.002-0.05 mg / cm 2 .

[0013] The ZnO-graphene nanocomposite material or the ZnS-graphene nanocomposite material is prepared by a hydrothermal method, that is, heating a graphene oxide solution containing 2% to 10% by mass of nano ZnO or nano ZnS in an autoclave.

[0014] The liquid precursor comprises the following components:

[0015] Polymer monomer: one of epoxy resin monomer, acrylonitrile (AN), vinyl ether monomer and acrylate monomer;

[0016] Solvent: including one of dimethyl carbonate (DMC), ethylene glycol dimethyl ether (G2), and propylene glycol dimethyl ether (G3);

[0017] Electrolyte salt: including one of lithium hexafluorophosphate (LiPF6), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(difluorosulfonyl)imide (LiFSI);

[0018] Photoinitiator: one of benzoin ether (BPOE), dimethyl benzoate (DBM), and 2,2-dimethoxy-2-phenylacetophenone (DMPA).

[0019] The liquid precursor is sprayed during the roll-to-roll process, and the mass percentage of the liquid precursor is 10%-40%, and the density is 0.5-3g / cm 3 The spraying thickness is 5-20 microns, and a uniform protective layer is formed by photoinitiated polymerization.

[0020] The method for preparing the metal lithium negative electrode of the composite polymer electrolyte protection layer also includes further processing the treated metal lithium negative electrode and cutting it into a specific size.

[0021] The metal lithium negative electrode of the composite polymer electrolyte protective layer prepared by the above preparation method.

[0022] The advantages and technical effects of the present invention are as follows:

[0023] 1. Promote uniform lithium deposition: The lithiophilic nanoparticles on the cellulose membrane help guide the uniform deposition of lithium ions and reduce the risk of lithium dendrite formation.

[0024] 2. Enhanced interface stability: The cellulose membrane and the nanomaterials on it work together to enhance the interface stability of the metal lithium negative electrode and improve the cycle life of the battery.

[0025] 3. Ensure coating uniformity: The presence of cellulose film enables the liquid precursor to be quickly and evenly dispersed, avoiding the unevenness caused by liquid sliding and local aggregation, ensuring that the final polymer electrolyte protective layer is flat and uniform, which is conducive to the uniform transport of lithium ions.

[0026] 4. Simplify the manufacturing process: The entire process is simple and easy, suitable for large-scale industrial production, and reduces manufacturing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the charge and discharge curve of the INP05 / 110 / 150 metal lithium battery obtained in Example 1 of the present invention.

[0028] Figure 2 This is the room temperature cycle curve of the INP05 / 110 / 150 lithium metal battery obtained in Example 1 of the present invention.

[0029] Figure 3 This is the rate discharge curve of the INP05 / 110 / 150 metal lithium battery obtained in Example 1 of the present invention.

[0030] Figure 4 This is the low temperature discharge curve of the INP05 / 110 / 150 metal lithium battery obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0032] The method for preparing the metal lithium negative electrode of the composite polymer electrolyte protective layer of the present invention comprises the following steps in sequence:

[0033] (1) spraying a layer of ZnO-graphene nanocomposite aqueous solution or ZnS-graphene nanocomposite aqueous solution on the surface of the cellulose film;

[0034] (2) laminating a layer of the cellulose film prepared in step (1) on the surface of the negative electrode of lithium foil or metal lithium alloy foil;

[0035] (3) spraying a liquid precursor that can be cured in situ on the cellulose film, and forming a metal lithium negative electrode with a uniform composite polymer electrolyte protective layer through photoinitiated polymerization.

[0036] The thickness of the lithium foil or metal lithium alloy foil is in the range of 10-80 microns.

[0037] The thickness of the cellulose film is in the range of 0.5-5 microns.

[0038] The concentration of the ZnO-graphene nanocomposite aqueous solution or the ZnS-graphene nanocomposite aqueous solution is 0.1 mg / ml-1 mg / ml, and the spraying amount is controlled at 0.002-0.05 mg / cm 2 .

[0039] The ZnO-graphene nanocomposite material or the ZnS-graphene nanocomposite material is prepared by a hydrothermal method, that is, heating a graphene oxide solution containing 2% to 10% by mass of nano ZnO or nano ZnS in an autoclave.

[0040] The liquid precursor comprises the following components:

[0041] Polymer monomer: one of epoxy resin monomer, acrylonitrile (AN), vinyl ether monomer and acrylate monomer;

[0042] Solvent: including one of dimethyl carbonate (DMC), ethylene glycol dimethyl ether (G2), and propylene glycol dimethyl ether (G3);

[0043] Electrolyte salt: including one of lithium hexafluorophosphate (LiPF6), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(difluorosulfonyl)imide (LiFSI);

[0044] Photoinitiator: one of benzoin ether (BPOE), dimethyl benzoate (DBM), and 2,2-dimethoxy-2-phenylacetophenone (DMPA).

[0045] The liquid precursor is sprayed during the roll-to-roll process, the mass percentage of the liquid precursor is 10%-40%, the density is 0.5-3g / cm3, the spraying thickness is 5-20 microns, and a uniform protective layer is formed by photo-induced polymerization.

[0046] The method for preparing the metal lithium negative electrode of the composite polymer electrolyte protection layer also includes further processing the treated metal lithium negative electrode and cutting it into a specific size.

[0047] The metal lithium negative electrode of the composite polymer electrolyte protective layer prepared by the above preparation method.

[0048] Specifically, it includes:

[0049] S1 Prepare substrate: Select lithium foil or metal lithium alloy foil of appropriate thickness and size as the base material.

[0050] S2 Nanomaterial pretreatment: Prepare nano ZnO or ZnS graphene nanomaterials into an aqueous solution. Use spraying technology to evenly coat the above nanomaterials on the surface of the cellulose membrane to ensure that the nanomaterials are evenly distributed and firmly attached.

[0051] S3 Cellulose membrane lamination: The cellulose membrane containing prefabricated nanomaterials is tightly pressed onto the surface of lithium foil or metal lithium alloy foil, ensuring that there are no bubbles or other defects between the two.

[0052] S4 Liquid Precursor Spraying and Curing: During the roll-to-roll process, a liquid precursor that can be cured in situ is sprayed on the surface of the metal lithium. Due to the good wettability of the cellulose membrane, the droplets can be quickly dispersed and evenly dispersed. Subsequently, a uniform polymer electrolyte protective layer is formed through photo-induced polymerization.

[0053] S5 post-processing: further processing is performed on the metal lithium negative electrode after the above treatment as needed, such as cutting into specific sizes, etc., to adapt to different battery design requirements.

[0054] Here are some specific examples:

[0055] Example 1

[0056] S1 Prepare substrate: Select lithium foil with a thickness of 20 microns as the base material

[0057] S2 Nanomaterial pretreatment: The ZnO-graphene nanocomposite material was prepared into an aqueous solution with a concentration of 0.2 mg / ml, and the above nanomaterial was evenly coated on the surface of the 2-micron cellulose membrane by spraying technology, and the spraying amount was controlled at 0.005 mg / cm 2 , ensuring that the nanomaterials are evenly distributed and firmly attached;

[0058] S3 Cellulose membrane pressing: Press the cellulose membrane containing prefabricated nanomaterials tightly onto the surface of lithium foil, ensuring that there are no bubbles or other defects between the two;

[0059] S4 Liquid Precursor Spraying and Curing: During the roll-to-roll process, the liquid precursor (PETDA+EOEOEA+LiFSi) that can be cured in situ is sprayed on the surface of the lithium metal. The density of the liquid precursor is 1.2g / cm 3 The spraying thickness is 10 microns. Due to the good wettability of the cellulose membrane, the droplets can be quickly dispersed and evenly dispersed. Then, a uniform polymer electrolyte protective layer is formed through photoinitiated polymerization.

[0060] S5 post-processing: further process the metal lithium negative electrode after the above treatment as needed, cut it into specific size, and assemble it with specific positive electrode plates into a model battery cell for corresponding testing.

[0061] Wherein, the preparation method of ZnO-graphene nanocomposite material is as follows:

[0062] 1) Dispersion: Graphene oxide (GO) was dispersed in deionized water and ultrasonicated for 1 h to ensure that the GO sheets were fully exfoliated and evenly dispersed.

[0063] 2) Dissolution: Dissolve the ZnO precursor Zn(NO3)2·6H2O in deionized water and stir evenly to form a transparent Zn 2+ Solution.

[0064] 3) Mixing: Mix the dispersed GO solution with Zn 2+ The solutions were mixed, the mass ratio of ZnO precursor to graphene oxide was 4:100, stirred evenly, and 1% by mass of ascorbic acid as a reducing agent was added.

[0065] 4) Hydrothermal reaction: The mixed solution is transferred to an autoclave, sealed and placed in an oven for hydrothermal reaction. The reaction temperature is usually between 170°C and the reaction time is 10 hours.

[0066] 5) Washing: After the reaction is completed, the product is centrifuged and washed several times with deionized water and ethanol to remove unreacted precursors and other impurities.

[0067] 6) Drying: Dry the washed product in a vacuum drying oven to obtain the final ZnO-graphene nanocomposite material.

[0068] The appearance of the INP05 / 110 / 150 lithium metal battery obtained in this embodiment is as follows: Figure 1 As shown, the electrical performance test was then carried out. The test results are shown in Figures 2-4. The battery has a nominal capacity of 14.6Ah, dimensions of 4.5×110×150mm, an energy density of up to 455Wh / kg (0.1C), an operating voltage of 3-4.35V, and a capacity retention rate of 82.69% after 200 cycles at room temperature, a 1C capacity retention rate of 95.8%, a 3C capacity retention rate of 91%, a low-temperature capacity retention rate of 82.1% (-20°C, 0.2C), and a high-temperature capacity retention rate of 103.7% (80°C, 0.2C).

[0069] Example 2

[0070] S1 Prepare substrate: Select lithium foil with a thickness of 20 microns as the base material

[0071] S2 Nanomaterial pretreatment: The ZnO-graphene nanocomposite material was prepared into an aqueous solution with a concentration of 0.2 mg / ml, and the above nanomaterial was evenly coated on the surface of the 2-micron cellulose membrane by spraying technology, and the spraying amount was controlled at 0.005 mg / cm 2 , ensuring that the nanomaterials are evenly distributed and firmly attached;

[0072] S3 Cellulose membrane pressing: Press the cellulose membrane containing prefabricated nanomaterials tightly onto the surface of lithium foil, ensuring that there are no bubbles or other defects between the two;

[0073] S4 liquid precursor spraying and curing: During the roll-to-roll process, the liquid precursor (TEGDMA+EOEOEA+LiFSi) that can be cured in situ is sprayed on the surface of the lithium metal. The density of the liquid precursor is 1.2g / cm 3 The spraying thickness is 10 microns. Due to the good wettability of the cellulose membrane, the droplets can be quickly dispersed and evenly dispersed. Then, a uniform polymer electrolyte protective layer is formed through photoinitiated polymerization.

[0074] S5 post-processing: further process the metal lithium negative electrode after the above treatment as needed, cut it into specific size, and assemble it with specific positive electrode plates into a model battery cell for corresponding testing.

[0075] The INP05 / 110 / 150 lithium metal battery obtained in this embodiment was subsequently subjected to electrical performance testing. The battery had a nominal capacity of 14.6 Ah and an overall size of 4.5×110×150 mm. The energy density was lower than that of Example 1. This was mainly due to the longer TEGDMA monomer molecular chain and the lower ionic conductivity of the polymer electrolyte, which resulted in a decrease in energy density.

[0076] Example 3

[0077] Compared with Example 1, the 2-micron cellulose membrane was replaced with a 4-micron cellulose membrane, and other conditions remained unchanged. The energy density of the final INP05 / 110 / 150 lithium metal battery was lower than that of Example 1. This is mainly because as the thickness of the cellulose membrane increases, the ionic conductivity of the battery decreases, and the weight increases, thereby reducing the energy density.

[0078] Example 4

[0079] Compared with Example 1, the amount of graphene nanomaterial sprayed is controlled at 0.005 mg / cm 2 The spraying amount of graphene nanomaterials is controlled at 0.01mg / cm 2 , other conditions remain unchanged, the energy density of the final INP05 / 110 / 150 lithium metal battery is lower than that of Example 1. This is mainly because as the thickness of the cellulose film increases, the ionic conductivity of the battery decreases, and the weight increases, thereby reducing the energy density.

[0080] Replacing the ZnO-graphene nanocomposite with a ZnS-graphene nanocomposite has the same effect, so it will not be given as an example here.

[0081] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a metal lithium negative electrode with a composite polymer electrolyte protective layer, characterized in that: The following steps are included in sequence: (1) spraying a layer of ZnO-graphene nanocomposite aqueous solution or ZnS-graphene nanocomposite aqueous solution on the surface of the cellulose film; (2) laminating a layer of the cellulose film prepared in step (1) on the surface of the negative electrode of lithium foil or metal lithium alloy foil; (3) spraying a liquid precursor that can be cured in situ on the cellulose film, and forming a metal lithium negative electrode with a uniform composite polymer electrolyte protective layer through photoinitiated polymerization.

2. The method for preparing a metal lithium negative electrode with a composite polymer electrolyte protective layer according to claim 1, characterized in that: The thickness of the lithium foil or metal lithium alloy foil is in the range of 10-80 microns.

3. According to the method for preparing a metal lithium negative electrode with a composite polymer electrolyte protective layer as claimed in claim 1, the thickness of the cellulose film is in the range of 0.5-5 microns.

4. The method for preparing a metal lithium negative electrode of a composite polymer electrolyte protective layer according to claim 1, characterized in that: The concentration of the ZnO-graphene nanocomposite aqueous solution or the ZnS-graphene nanocomposite aqueous solution is 0.1 mg / ml-1 mg / ml, and the spraying amount is controlled at 0.002-0.05 mg / cm 2 .

5. The method for preparing a metal lithium negative electrode of a composite polymer electrolyte protective layer according to claim 1, characterized in that: The ZnO-graphene nanocomposite material or the ZnS-graphene nanocomposite material is prepared by a hydrothermal method, that is, heating a graphene oxide solution containing 2% to 10% by mass of nano ZnO or nano ZnS in an autoclave.

6. The method for preparing a metal lithium negative electrode with a composite polymer electrolyte protective layer according to claim 1, characterized in that: The liquid precursor comprises the following components: Polymer monomer: one of epoxy resin monomer, acrylonitrile (AN), vinyl ether monomer and acrylate monomer; Solvent: including one of dimethyl carbonate (DMC), ethylene glycol dimethyl ether (G2), and propylene glycol dimethyl ether (G3); Electrolyte salt: including one of lithium hexafluorophosphate (LiPF6), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(difluorosulfonyl)imide (LiFSI); Photoinitiator: one of benzoin ether (BPOE), dimethyl benzoate (DBM), and 2,2-dimethoxy-2-phenylacetophenone (DMPA).

7. The method for preparing a metal lithium negative electrode with a composite polymer electrolyte protective layer according to claim 1, characterized in that: The liquid precursor is sprayed during the roll-to-roll process, and the mass percentage of the liquid precursor is 10%-40%, and the density is 0.5-3g / cm 3 The spraying thickness is 5-20 microns, and a uniform protective layer is formed by photoinitiated polymerization.

8. The method for preparing a metal lithium negative electrode with a composite polymer electrolyte protective layer according to claim 1, characterized in that: It also includes further processing the treated metallic lithium negative electrode and cutting it into specific sizes.

9. A metallic lithium negative electrode with a composite polymer electrolyte protective layer obtained by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Lithium metal double-layer protection layer and lithium metal negative electrode interface modification method

    CN115692706A

  • Preparation method of lithium-sulfur secondary battery

    CN102956923A

  • Solid-state composite metal lithium negative electrode

    CN108511708A

  • Lithium iron phosphate / gel electrolyte composite positive electrode material, preparation method thereof, solid-state lithium battery and preparation method of solid-state lithium battery

    CN108550835A

  • Electrolyte membrane of solid battery, preparation method for electrolyte membrane and solid battery with electrolyte membrane

    CN109286039A